Preliminary COI analysis reveals a divergent Carcinoscorpius lineage in North Kalimantan, Indonesian Borneo - MOHAMMAD FADNAN AKHMADI; SUTRISNO ANGGORO; AGUS SABDONO; ANINDITIA SABDANINGSIH; DIAH AYUNINGRUM; ASBAR LAGA; ENCIK WELIYADI (Society for Indonesian Biodiversity, 2026)
Abstract. Akhmadi MF, Anggoro S, Sabdono A, Sabdaningsih A, Ayuningrum D, Laga A, Weliyadi E. 2026. Preliminary COI-based identification of selected horseshoe crab vouchers indicates a divergent Carcinoscorpius mitochondrial lineage in North Kalimantan, Indonesian Borneo. Biodiversitas 27 (8): d270805. https://doi.org/10.13057/biodiv/d270805. Molecular records of Asian horseshoe crabs from North Kalimantan are limited, constraining assessments of taxonomic affinity and mitochondrial variation in Indonesian Borneo. This study examined four morphologically selected voucher specimens from Karis and Mangkudulis islands using mitochondrial Cytochrome C Oxidase subunit I (COI) sequences. The trimmed sequences (653-661 bp) were quality-checked against a common 649-bp homologous region. Phylogenetic and K2P analyses used a 20-sequence, 624-bp alignment, while ASAP and haplotype analyses used the corresponding 19-sequence ingroup matrix. KU1PMTG1 showed 99.85% BLASTn identity to Tachypleus gigas, whereas KU1PKTT4 showed 99.24% identity to T. tridentatus; both assignments were supported by BOLD, low K2P distances, and consistent phylogenetic placement. In contrast, KU1PKCR2 and KU2PKCR3 shared an identical COI haplotype but showed only 91.99% and 91.78% identity to their closest Carcinoscorpius rotundicauda matches. Their K2P divergence from selected C. rotundicauda references ranged from 8.60% to 9.51%, exceeding the 0-1.29% variation within the reference group. The two North Kalimantan sequences formed a strongly supported phylogenetic subclade, a distinct ASAP operational subset, and a haplotype separated by 50 mutational steps from the nearest selected C. rotundicauda haplotype. These concordant patterns indicate a deeply differentiated Carcinoscorpius-affiliated mitochondrial lineage, suggesting potential cryptic diversity or an unsampled regional lineage. However, because this inference is based on two unresolved specimens, one mitochondrial marker, and forward-direction sequencing, they are conservatively retained as putative Carcinoscorpius sp. Broader Borneo sampling, bidirectional sequencing, nuclear markers, and diagnostic morphological comparisons are required to clarify their taxonomic status.